Analysis of Financial Management of Kembang Village in Simalungun Regency - Ramadhan, Puja Rizqy (CERED Indonesia Institute, 2025)
The objective of this study is to analyze how the local government, particularly the administration of Kembang Village, manages village funds and financial assets. This study employs a qualitative research approach. The research subjects include ten individuals: the Village Head, Village Secretary, Village Treasurer, Hamlet Head, Neighborhood/Community Unit Leaders (RT/RW), Community Leaders, and local community members. Data collection methods in this study consist of observations, interviews, and document analysis. The findings indicate that the Kembang Village government manages finances effectively, adhering to the principles of transparency and high community participation. Additionally, several factors hinder the management of village assets.